Ideal Anatomical Landmark Points for Thoracic Esophagus Segmentation in the Chinese Population - Lu, Di; Ji, Xiuyu; Zhan, Jintao; Zhai, Jianxue; Fang, Tingxiao; Feng, Siyang; Liu, Xiguang; Yu, Lin; Chen, Zhiming; Wang, Zhizhi; Wu, Xuanzhen; Liu, Sue; et al. (Frontiers in Surgery, 2021)
Introduction: The standards of esophagus segmentation remain different between the Japan Esophageal Society (JES) guideline and the Union for International Cancer Control (UICC)/American Joint Committee on Cancer (AJCC) guideline. This study aimed to present variations in the location of intrathoracic esophageal adjacent anatomical landmarks (EAALs) and determine an appropriate method for segmenting the thoracic esophagus based on relatively fixed EAALs. Patients and methods: The distances from the upper incisors to the upper border of the esophageal hiatus, lower border of the inferior pulmonary vein (LPV), tracheal bifurcation, lower border of the azygous vein (LAV), and thoracic inlet were measured in patients undergoing thoracic surgery. Median distances between EAALs and the specified starting points, as well as reference value ranges and ratios, were obtained. The variation coefficients of distances and ratios from certain starting points to different EAALs were calculated and compared to determine the relatively fixed landmarks. Results: This study included 305 patients. The average distance from the upper incisors to the upper border of the cardia, the midpoint between the tracheal bifurcation and esophageal hiatus (MTBEH), LPV, LAV, tracheal bifurcation, and thoracic inlet were 41.6 cm, 35.3 cm, 34.8 cm, 29.4 cm, 29.5 cm, and 20.3 cm, respectively. The distances from the upper incisors or thoracic inlet to any intrathoracic EAALs in males were higher than in females. Height, weight, and body mass index (BMI) were also correlated with the distances. The ratio of the distance between the upper incisors and tracheal bifurcation to the distance between the upper incisors and upper border of the cardia and the ratio of the distance between the thoracic inlet and tracheal bifurcation to the distance between the thoracic inlet and upper border of the cardia possessed relatively smaller coefficients of variation. Conclusion: The distances from the EAALs to the upper incisors vary with height, weight, BMI, and gender. Compared with distance, the ratios are more suitable for esophagus segmentation. Tracheal bifurcation and MTBEH are ideal EAALs for thoracic esophagus segmentation, and this is consistent with the JES guideline recommendation.